Monte Carlo study of the magnetic properties and finite size effects in single wall ferromagnetic nanotubes (2012)
ABSTRACT: In this work the influence of diameter upon the magnetic properties of single wall ferromagnetic nanotubes was studied. Magnetization per site, magnetic susceptibility, specific heat and total energy were computed on the basis of a classical Heisenberg model involving nearest neighbor interactions and using a Monte Carlo method implemented with a single spin movement Metropolis dynamics. The spontaneous magnetization, absolute value of ferromagnetic energy and critical temperature increase with diameter of the tubes and spin quantum number. The critical temperature is determined by the tube diameter. As the diameter of the tube tends to infinity, all the numerical results approach to those of a two-dimensional monolayer